Convergence or Divergence in Theology of Religions? - Kjøde, Rolf (Mission studies, 2017)
If there is an ongoing convergence in understanding of mission between the two traditions of the global church named as conciliar and evangelical, can we trace this in the theology of religions? This study investigates this question by studying two recent and comprehensive mission documents, Together towards Life (ttl) and the Cape Town Commitment (ctc). Theology of religions is a topic fundamental and decisive for understanding the nature of Christian mission. The article concludes that the World Council of Churches (wcc) seemed to come closest to the evangelical theology of religions in the years leading up to 1989. Through ttl, the wcc officially seems to confirm an inclusivism with a wider opening towards pluralist aspects. The evangelical emphasis on proclamation, truth and uniqueness of Christ in ctc is not compatible with this development. A shift of direction in theology of religions since 1989 is detectable in ttl, while evangelical theology of religions is relatively stable in its fundamental thinking.